ChemInform Abstract: Catalytic Application of Task Specific Ionic Liquid on the Synthesis of Benzoquinazolinone Derivatives by a Multicomponent Reaction. Issue 22 (3rd June 2014) - Rahman, Matiur; Sarkar, Anirban; Ghosh, Monoranjan; Majee, Adinath; Hajra, Alakananda
Abstract Sulfobutyl substituted ionic liquid (IMS) efficiently catalyzes the Biginelli reaction of α‐tetralone, aldehyde, and urea or thiourea to afford benzoquinazoline derivatives.